Effectiveness of SMART System in Managing Jakarta MRT Project Loans and Grants - Alpa Pedro Immanuel Simorangkir; Riki Satia Muharam (International Journal of Multidisciplinary Sciences and Arts, 2026)
This study examines the initial effectiveness of the Loan and Grant Withdrawal System implemented by the Regional Financial Management Agency of DKI Jakarta Province in managing loan and grant funds for the Jakarta Mass Rapid Transit project. This research is motivated by the previous manual financial management process which resulted in delayed verification, frequent document revisions, limited tracking access, and inefficiencies that potentially increased project risks and financial penalties. The objective of this study is to analyze the effectiveness of the digital system and identify supporting and inhibiting factors during its early implementation stage. This research uses a qualitative descriptive approach through in depth interviews, direct observations, and document analysis involving officers from the Regional Financial Management Agency and Jakarta Mass Rapid Transit Company. The research findings indicate that the implementation of the digital system has significantly improved processing speed, data accuracy, document management, and transparency in financial reporting. The system enables real time monitoring, reduces administrative errors, and strengthens accountability in public financial governance. Users also expressed higher satisfaction due to automated validation features and a more structured workflow process. However, technical constraints and limited user training were identified as challenges that need to be addressed for optimal system utilization. This study concludes that the digital withdrawal system is effective in improving the management of loan and grant funds for large scale infrastructure projects. Further development and continuous evaluation are recommended to enhance system performance and sustainability in public financial management.